2022
DOI: 10.3389/fmed.2021.783982
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of COVID-19 Vaccination Acceptance

Abstract: IntroductionVaccination is an essential intervention to curb the coronavirus disease 2019 (COVID-19) pandemic. This review aimed to estimate the pooled proportion of COVID-19 vaccine acceptance worldwide.MethodsA systematic search of the MEDLINE (PubMed) database using “COVID-19,” “vaccine” and “acceptance” to obtain original research articles published between 2020 and July 2021. Only studies with full text and that were published in English were included. The Joanna Briggs Institute meta-analysis was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
64
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 193 publications
9
64
6
Order By: Relevance
“…The core concept of “uncertainty” in our study captured various aspects of uncertainty related to COVID-19 vaccination identified in previous studies [ 39 , 40 , 41 ], including the speed of development, perceived lack of sufficient testing, and long-term side effects. Past research comparing three hypothetical vaccine scenarios of vaccines being approved in one week, one year, or in two years, found that the shortest-term scenario was associated with significantly lower perceived vaccine efficacy and higher vaccine risks than the longer duration scenarios [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The core concept of “uncertainty” in our study captured various aspects of uncertainty related to COVID-19 vaccination identified in previous studies [ 39 , 40 , 41 ], including the speed of development, perceived lack of sufficient testing, and long-term side effects. Past research comparing three hypothetical vaccine scenarios of vaccines being approved in one week, one year, or in two years, found that the shortest-term scenario was associated with significantly lower perceived vaccine efficacy and higher vaccine risks than the longer duration scenarios [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient evidence for COVID-19 vaccine effectiveness was identified as a leading reason for reduced confidence in vaccines among the general population identified in a systematic review and meta-analysis of 172 studies of approx. 800,000 people from 50 countries [ 41 ]. These uncertainties relate to individual risk perception via “ambiguity aversion”, where risks are avoided when the outcome is uncertain [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rapid vaccine development process and implementation of vaccination campaigns against COVID-19, vaccination acceptance continues to be a challenge for health authorities [ 5 ]. Previous systematic reviews have found global vaccination acceptance rates ranging from 61 to 73% [ 6 , 7 ]. Also, these reviews highlight the great variability in vaccination acceptance rates depending on the geographic location.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, information on vaccine acceptance rates and its distribution across different population subgroups is needed. However, currently available reviews that synthetize vaccination acceptance rates mainly include studies from Europe and North America [ 6 , 7 ]. This could be explained by the databases used to conduct the search and the language restrictions when including the individual studies.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, healthcare personnel who were not directly in contact with these patients reported greater hesitancy. However, a generally higher acceptance of vaccination among healthcare workers with respect to the general population was reported in the literature [ 25 ].…”
Section: Introductionmentioning
confidence: 99%